Religious affiliation and perceptions of healthcare access during and after COVID-19 in Poland - Tuczyńska, Magdalena; Matthews-Kozanecka, Maja; Baum, Ewa (Frontiers in Public Health, 2025)
IntroductionIn response to the unprecedented impact of the COVID-19 pandemic on healthcare systems and social life worldwide, this study examines the role of religion in shaping perceptions of healthcare access in Poland during and after the pandemic.MethodsThe research is based on anonymous surveys conducted among adult Poles during the third wave of the pandemic and in the post-pandemic period, with participants divided by the timing of their responses. The research employed a cross-sectional survey design with a validated questionnaire. Data collection occurred during the third wave of the pandemic and the post-pandemic period. The questionnaire incorporated demographic questions and assessed the significance of religion in respondents' lives using a Visual Analogue Scale (VAS) for healthcare accessibility.ResultsParticipants (n = 541) were recruited through online and paper-based surveys, meeting the inclusion criteria of being aged 18 or older and residing in Poland. Findings indicate that Roman Catholic respondents rated healthcare accessibility higher than non-religious individuals, potentially due to social and community support. However, statistical analysis revealed no significant differences in actual healthcare access among groups, suggesting systemic factors played a larger role.DiscussionThese results highlight religion as a source of emotional support rather than a determinant of healthcare access.